Analysis of the Application "Pekanbaru Dalam Gengaman" in Relation to Digitalization of Services Using the Harvard JFK School of Government Approach: Analisis Aplikasi “Pekanbaru Dalam Genggaman” Kaitanya Pada Digitalisasi Pelayanan Menggunakan Pendekatan Harvard JFK School Of Government - Muliawan, Muhammad Arif; Harirah, Zulfa (JOURNAL OF GOVERNMENT SCIENCE, 2024)
The phenomenon of digital literacy has become a hot topic of discussion during the Covid-19 pandemic. Digital transformation in various community activities and public services managed by the government during the pandemic continues to this day. One of the innovations made by the Pekanbaru City Government is to create an electronic-based government application, namely "Pekanbaru Dalam Genggaman". This study aims to determine the effectiveness of using the "Pekanbaru Dalam Genggaman" application in providing public services to the community in relation to the digitalization of services. This study uses a qualitative approach where data sources are obtained from direct observation of the Pekanbaru Dalam Genggaman application and through literature studies of books, journals, articles, and other sources that are in accordance with the research topic. To analyze the concepts of digitalization in public services, this study uses an approach from the Harvard JFK School of Government, there are three elements of success that must be possessed, namely support, capacity, and value (benefits). The results of this study suggest that to apply the concepts of digitalization to public services, there are three elements of success that must be possessed, namely support, ability, and benefits. In terms of support, the government has deployed two to four IT personnel in each agency, but the infrastructure to support public services through digital is not yet optimal. In terms of capability, it is also considered unsuccessful, because 5 of the 16 features in the Pekanbaru Dalam Genggaman application do not function, of which 3 of the 5 features that do not function are very important for the community. In terms of benefits, only a small portion of the community feels the benefits. Because there are still many people who do not know about the existence of this application.